20 anos de sol: a espacialização dos empreendimentos de energia solar fotovoltaica no Ceará - Brasil - Chaves, Débora Raquel Freitas da Silva (2022)
Solar radiation is the essential condition for the development of life in the biosphere. Without solar radiation there is no life. On the other hand, this same radiation, in the context of Ceará's geographic space, has marked societies with paths of drought, hunger and scarcity. The fact is that the sun's rays are fundamental to make possible the multiform sources of energy on the planet. Faced with the society that has energy as an essential element in its socioeconomic organization, photovoltaic solar energy appears as a new alternative for Ceará space. Thus, the general objective of the research was to investigate the production of Ceará space from the generation of energy by photovoltaic solar source. The specific objectives of the research were to analyze the expansion and development of photovoltaic solar energy production in Brazil and Ceará, distinguishing production in generating plants and distributed generation and identifying the main producing agents in the space; discuss the public policies that have been implemented by the State for structuring photovoltaic solar energy in Ceará; analyze the legal frameworks for reducing bureaucracy/flexibilization of environmental licensing processes for photovoltaic solar energy projects; and recognize how photovoltaic solar energy has been (re)produced in Ceará, highlighting the challenges and overcoming. To this end, a path of investigation was traced that, as the readings were made and the fieldwork carried out, the practice versus theory relationship improved. The work included a bibliographic and documentary survey, as well as fieldwork in solar PV power plants. It was found that the real problem of the "excess sun" in the semiarid region is likely to become a great solution, that is, the sun can be configured as a vector of development and production of Ceará space. It is necessary to encourage the State itself to distributed generation and legal regulation to reduce tariffs and taxes for the final consumer with regard to centralized generation.